Assessment of dam function deterioration due to landslide-debris flows: numerical modeling based on vegetation distribution scenarios - Lee, Seungjun; An, Hyunuk; Kim, Minseok; Kang, Taeun (Frontiers in Earth Science, 2023)
Landslides are prevalent natural disasters in mountainous regions worldwide, and the debris flows that accompany them are considered a significant cause of topographical changes. Landslide-debris flows cause property damage and casualties if they occur in densely populated areas, such as cities and rural areas. Sediments entering a dam or reservoir lake can compromise the integrity and functionality of the facility. To minimize such damage, this phenomenon should be elucidated through numerical models and quantitative analyses performed. Despite South Korea having approximately 18,000 dams and reservoirs, with approximately 70% of the country being mountainous, research on landslides and debris flows occurring in the dam and reservoir basins remains insufficient. However, such studies are essential for the continuous operation and management of dams/reservoirs. This study focused on analyzing the damage caused by landslidedebris flow events in a dam or reservoir basin. We established different scenarios based on the distribution of vegetation in the basin to determine the impact of vegetation on slope stability and debris flows.